2006
DOI: 10.1634/stemcells.2006-0281
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Stem Cells Are Regionally Specified According to Local Microenvironments After Implantation for Cartilage Regeneration

Abstract: We previously demonstrated that synovium-derived MSCs had greater in vitro chondrogenic ability than other mesenchymal tissues, suggesting a superior cell source for cartilage regeneration. Here, we transplanted undifferentiated synovium-derived MSCs into a full-thickness articular cartilage defect of adult rabbits and defined the cellular events to elucidate the mechanisms that govern multilineage differentiation of MSCs. Full-thickness osteochondral defects were created in the knee; the defects were filled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
156
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 47 publications
5
156
1
6
Order By: Relevance
“…8 Furthermore, synovial MSCs were shown capable of rabbit cartilage repair. 9 These results indicated that synovium represents a precious source of MSCs, and also opened new approaches for combating synovial inflammation, by interfering with signaling pathways involved in MSC differentiation.…”
mentioning
confidence: 92%
“…8 Furthermore, synovial MSCs were shown capable of rabbit cartilage repair. 9 These results indicated that synovium represents a precious source of MSCs, and also opened new approaches for combating synovial inflammation, by interfering with signaling pathways involved in MSC differentiation.…”
mentioning
confidence: 92%
“…[1][2][3][4] MSCs can be obtained from a variety of mesenchymal tissues including bone marrow, 5 which seems to be the most popular MSC source at present. Synovium, a thin membrane covering the inside of joints, is another promising MSC source due to its high chondrogenic potential.…”
mentioning
confidence: 99%
“…For cartilage regeneration and repair, stem cells are an attractive cell source due to their superior capacity for self-renewal, proliferation, and response to stress (11,12). Results of several studies have suggested that various stem cells have potential for cartilage regeneration and repair in experimental cartilage injury models (13)(14)(15). Recently, autologous stem cell-based tissue engineering has been used clinically for cartilage repair and regeneration (16,17).…”
mentioning
confidence: 99%